2013
DOI: 10.2217/pgs.13.80
|View full text |Cite
|
Sign up to set email alerts
|

CYP3A4*22 and CYP3A Combined Genotypes Both Correlate With Tacrolimus Disposition in Pediatric Heart Transplant Recipients

Abstract: Analysis of CYP3A4*22, either alone or in combination with CYP3A5*3, may help towards individualization of tacrolimus therapy in pediatric heart transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 24 publications
5
44
2
Order By: Relevance
“…Another study found that the rs4646437 C>T polymorphism could potentially affect the interindividual variability in tacrolimus metabolism among Chinese renal transplant recipients [33]. Tacrolimus is metabolized mainly by CYP3A4 and CYP3A5 [34]. This finding is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…Another study found that the rs4646437 C>T polymorphism could potentially affect the interindividual variability in tacrolimus metabolism among Chinese renal transplant recipients [33]. Tacrolimus is metabolized mainly by CYP3A4 and CYP3A5 [34]. This finding is consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…[36][37][38] In pediatric heart transplantation, an association between CYP3A4*22 and Tac dose requirement has also been observed. [39] CYP3A4*22 carriers needed 30% less Tac to reach similar target concentrations compared with CYP3A4*1/*1 carriers.…”
Section: Cyp3a4mentioning
confidence: 91%
“…7,[9][10][11] Recently, a novel functional polymorphism in CYP3A4 (CYP3A4*22; rs35599367) was described and associated with lower CNI dose requirement in transplant patients. [12][13][14][15] Furthermore, polymorphisms in the P450 oxidoreductase (POR gene) and pregnane X receptor (PXR, NR1I2 gene) have been shown to modulate the activity of CYP3A enzymes and to alter the pharmacokinetics of TAC in kidney transplant patients. 16,17 Studying multiple polymorphisms in genes acting together on an immunosuppressive drug pathway instead of single variants may provide new insight into factors influencing the response.…”
Section: Introductionmentioning
confidence: 99%